The Potential of Iron Supplementation in Pregnant Women with Gestational Diabetes Mellitus: A Literature Review - Siti Aisyah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Iron supplementation in pregnant women is one of the key interventions recommended to prevent anemia and support the health of both the mother and the fetus. The increased need for iron during pregnancy makes supplementation a primary strategy in maternal health care. However, it is important to note that excessive iron intake has the potential to cause side effects such as iron overload, which can increase oxidative stress and insulin resistance in pregnant women. These conditions are suspected to contribute to an increased risk of pregnancy complications, one of which is Gestational Diabetes Mellitus (GDM). Objective: This study aims to determine the effect of iron (Fe) supplementation on the risk of gestational diabetes mellitus during pregnancy. Methods: This study employed a literature review design. Article retrieval was conducted through three databases—Google Scholar, DOAJ, and PubMed—using the keywords “iron supplementation,” “iron supplementation,” and “gestational diabetes risk.” Inclusion criteria included articles published between 2018 and 2023. The search yielded 5 relevant articles for comprehensive review. Results: Analysis of the selected articles indicates a trend toward an increased risk of GDM in pregnant women receiving iron supplementation, particularly when iron levels are already high. Therefore, the administration of iron supplements should be approached with caution if a pregnant woman has GDM. Conclusion: Iron supplementation is associated with an increased risk of GDM; therefore, its use should be tailored to the individual needs of the pregnant woman.